Magnetic ground survey of Slovakia for the 2007.5 epoch – accuracy of geomagnetic elements distribution maps - Peter DOLINSKÝ (Contributions to Geophysics and Geodesy, 2013)
Magnetic ground or repeat station surveys are performed to determine the geomagnetic field (GMF) spatial distribution, which is of great importance for scientific purposes as well as for many applications, for instance the aerial navigation. In for the information about the GMF distribution to be complete, the accuracy of the geomagnetic maps need to be known. It is a custom in the papers dealing with magnetic surveys that the precision of the instruments employed for the measurements are listed there. However, such information is not sufficient to answer the question about the quality of the geomagnetic maps because our experience shows that the spatial variations at a distance of several kilometers often exceed the precisions of the instruments. In the paper we proposed a simple method for the evaluation of the accuracy of the GMF distribution maps. We applied it to the maps which were the results of the magnetic ground survey carried out in Slovakia in the 2007.5 epoch. The method is based on the following procedure which is accomplished for each observation point of the magnetic ground survey network: A single point drops out of the data base, then the map is generated in a standard way, whereupon the observed value of the geomagnetic element for the dropped out observation point is compared with the value of the geomagnetic element which is determined from the map. Thus the image of the accuracy of the complete map can be tagged together for the surveyed territory.